Estradiol modulates the palatability of 0.3 M NaCl in female rats during sodium appetite - Pereira, E. D. [UNESP]; Dantas, R. M. [UNESP]; Andrade-Franzé, G. M.F. [UNESP]; De Luca, L. A. [UNESP]; Menani, J. V. [UNESP]; Andrade, C. A.F. [UNESP] (Elsevier, 2019)
Excessive salt intake has been associated with the development or worsening of chronic diseases such as hypertension and spontaneously hypertensive rats (SHR) have a typical increased sodium preference. Estrogens reduce sodium appetite, but we do not know whether such effect relates to alterations in sodium palatability. Here we evaluated the influence of ovarian hormones on orofacial motor responses, an index of palatability, to intra-oral infusion of 0.3 M NaCl (IO–NaCl). Adult female SHR and normotensive Holtzman rats (HTZ) were used. Sodium appetite was produced by water deprivation followed immediately by partial rehydration by drinking water to satiation (WD-PR protocol). Immediately at the end of WD-PR, animals received an IO-NaCl for videotape recording of orofacial motor responses. At the end of IO-NaCl, they had access to two bottles containing 0.3 M NaCl and water to ingest (sodium appetite test). Bilateral ovariectomy (OVX) enhanced 0.3 M NaCl intake during the sodium appetite test and increased the frequency of orofacial hedonic responses to IO-NaCl in both strains. It had no effect on aversive responses. Estradiol treatment in SHR-OVX decreased hedonic responses and increased aversive responses to IO-NaCl. It also reduced 0.3 M NaCl intake during the sodium appetite test, but had no effect on baseline mean arterial pressure and heart rate. The results suggest that ovarian hormones restrain WD-PR-induced sodium appetite by reducing the hedonic properties of sodium taste. The results also suggest that estrogens mediate such reduction, particularly in SHR.
Keywords: Dehydration; Hypertension; Reward; Sodium appetite; Taste; Water deprivation